SOCIAL RESPONSIBILITY OF BUSINESS AS A STRATEGIC FACTOR OF SUSTAINABLE DEVELOPMENT IN THE CONDITIONS OF POST-WAR RECONSTRUCTION - GURSKIY, Artem (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines corporate social responsibility (CSR) as a strategic factor in sustainable development within the context of Ukraine’s post-war reconstruction. It is substantiated that the large-scale needs of economic and social recovery actualize the necessity of a profound transformation of corporate strategies. It is shown that business cannot be limited to fragmentary charitable practices characteristic of wartime but must integrate the principles of ESG (environmental, social, and governance standards) and the Sustainable Development Goals (SDGs) into its business models. Modern scientific approaches to the institutionalization of CSR in the international and national context are analyzed. The concept of Creating Shared Value (CSV), the Triple Bottom Line paradigm, as well as contemporary studies confirming the positive impact of ESG practices on the investment attractiveness and financial performance of companies, are considered. It is substantiated that for Ukraine in the post-war period, such approaches acquire strategic importance, as they ensure transparency, accountability, and alignment with international standards of sustainable development. A three-level model of CSR and ESG integration into corporate strategies is proposed. The conceptual level defines the values and strategic vision of the business; the managerial level provides institutionalization, reporting, and transparency; while the practical level focuses on implementing economic, social, environmental, and digital projects. It has been proven that the implementation of this model ensures a transition from reactive to systemic CSR practices, contributes to increasing the investment attractiveness of businesses, and aligns national reconstruction with international standards of sustainable development. The practical significance of the results lies in the possibility of applying the proposed model to develop national standards for non-financial reporting, create indicators of social impact, and enhance the efficiency of recovery processes.